2022
DOI: 10.1007/s12975-022-01101-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of New-Generation Antiepileptic Drug Prophylaxis on Delayed Neurovascular Events After Aneurysmal Subarachnoid Hemorrhage

Abstract: Neuroelectric disruptions such as seizures and cortical spreading depolarization may contribute to the development of delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (SAH).However, effects of antiepileptic drug prophylaxis on outcomes remain controversial in SAH. The authors investigated if prophylactic administration of new-generation antiepileptic drugs levetiracetam and perampanel was bene cial against delayed neurovascular events after SAH. This was a retrospective single-center co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…33 Although we identified no patients with thalamic, midbrain, or pons infarction, the latter 2 cannot be adequately assessed in CT imaging and it is possible MRI would yield different results. In a recent study by Suzuki et al, 34 the role of microvascular infarction was highlighted after performing routine MRI in patients with SAH on admission and at discharge. Congruous to ischemic stroke research, routine MRI in future prospective studies could allow for voxel-based lesion symptom mapping specific to DCI-related infarction.…”
Section: Discussionmentioning
confidence: 99%
“…33 Although we identified no patients with thalamic, midbrain, or pons infarction, the latter 2 cannot be adequately assessed in CT imaging and it is possible MRI would yield different results. In a recent study by Suzuki et al, 34 the role of microvascular infarction was highlighted after performing routine MRI in patients with SAH on admission and at discharge. Congruous to ischemic stroke research, routine MRI in future prospective studies could allow for voxel-based lesion symptom mapping specific to DCI-related infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Phenytoin as ASM should be avoided since it may induce harm. In an underpowered, prospective, single-centre, randomized, open-label trial, the benefit from prolonged levetiracetam prophylaxis was greatest for those with imaging evidence of early brain injury [ 65 ] and others have suggested a possible benefit against DCI with newer ASMs (levetiracetam and perampanel) [ 66 ]. All clinical or electrographic seizures that are diagnosed should be treated for at least 7 days and for those with delayed seizures or those with risk factors for seizures, more prolonged treatment should be considered.…”
Section: Intracranial Complicationsmentioning
confidence: 99%
“…Thus, PEDF may be upregulated in brain tissues by ischemic injuries associated with EBI [14,16]. The severity of EBI is known to be correlated with admission WFNS grades [34], and more severe EBI is more likely to lead to angiographic vasospasm-related DCI or vasospasm-unrelated DCI and poor outcomes [30,33,37]. In this study, because angiographic vasospasm was not associated with outcome, it is suggested that EBI itself or DCI unrelated to vasospasm may be more important for poor outcome in elderly SAH patients.…”
Section: Pedf and Early Brain Injury (Ebi)mentioning
confidence: 99%